2019
DOI: 10.1055/s-0039-1683982
|View full text |Cite
|
Sign up to set email alerts
|

Severe Anemia Is Associated with Intestinal Injury in Preterm Neonates

Abstract: Objective A temporal relationship has been reported between necrotizing enterocolitis, anemia, and red blood cell transfusion (RBCT) in preterm neonates. However, the mechanism underlying this association is not clearly defined. Intestinal (I-) and liver (L-) fatty acid binding proteins (FABPs) have been proposed as plasma markers for the detection of acute intestinal injury. This study aimed to investigate the effect of anemia and RBCT on intestinal injury in preterm neonates by measuring serum I-FABP and L-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
(24 reference statements)
0
13
0
Order By: Relevance
“…Recent concerns regarding the association between RBC transfusions and the development of necrotizing enterocolitis (NEC) may have further restricted transfusion policies in preterm infants. 5 However, anemia itself resulting in tissue hypoxia may also cause intestinal injury, 6 8 as is also supported by the results of two preclinical studies. 9 , 10 It remains unclear, whether this increased risk of NEC is related mainly to the transfusion or to the anemia itself.…”
Section: Introductionmentioning
confidence: 77%
“…Recent concerns regarding the association between RBC transfusions and the development of necrotizing enterocolitis (NEC) may have further restricted transfusion policies in preterm infants. 5 However, anemia itself resulting in tissue hypoxia may also cause intestinal injury, 6 8 as is also supported by the results of two preclinical studies. 9 , 10 It remains unclear, whether this increased risk of NEC is related mainly to the transfusion or to the anemia itself.…”
Section: Introductionmentioning
confidence: 77%
“…Our previous clinical trial found that the improvement of severe anemia reduced the incidence of NEC in preterm infants, which also suggested the impact of anemia on the development of NEC [19]. A prospective cohort study showed that anemia was associated with intestinal injury [33]. The possible mechanism is that anemia can reduce tight junction protein ZO-1 expression, increase intestinal barrier permeability, and increase intestinal inflammation through altered macrophage function, leading to intestinal injury that may increase the risk of NEC [20,21].…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the critical value for abdominal tissue desaturation is noted when the HCT is less than 24%, predisposing premature infants for necrotizing enterocolitis and intestinal injury. [23][24][25] AOP also reported to be associated with increased incidence of intermittent hypoxic episodes in premature infants, especially after the first month of life, and RBC transfusions has been associated with reduction in apnea frequency in the short term. 26,27 In our study, premature infants with severe AOP during initial PO were more premature at birth, compared with controls.…”
Section: Discussionmentioning
confidence: 97%